The Naturopathic Approach in the Management of Bilateral Hydronephrosis: A Single Case Study - Sivaranjani, Dr. N.; Tamilarasu, Dr. T.; Pandiaraja, Dr. M. (Indian Journal of Integrative Medicine, 2025)
Bilateral hydronephrosis, which is characterized by the dilation of the renal pelvis and ureters due to urine outflow obstruction, can cause severe renal dysfunction and complications. This case report assesses the efficacy of naturopathic interventions, such as hydrotherapy and a plant-based low-protein diet (PLADO), in treating bilateral hydronephrosis and improving patient quality of life. A 37-year-old woman diagnosed with Grade 1 bilateral hydronephrosis reported severe lower back pain, abdominal discomfort, and psychological distress. Following informed consent, a three-month treatment protocol consisting of renal packs, ginger packs, steam baths, and dietary modifications was implemented. Post-treatment assessments demonstrated a significant reduction in serum creatinine levels from 2.9 mg/dl to 1.3 mg/dl, while serum potassium decreased from 5.5 mmol/l to 4.2 mmol/l, indicating improved renal function. Patient-reported outcomes revealed significant pain relief (VAS score improved from 8/10 to 3/10) and decreased levels of depression, anxiety, and stress according to the DASS21 scale. This case demonstrates the efficacy of naturopathic interventions, including hydrotherapy and dietary management in improving renal function and overall quality of life in patients with bilateral hydronephrosis. Further research involving larger populations is necessary to validate these findings and assess the broader applicability of these treatment strategies.